A magyar bankrendszer fejlődésének két évszázada: helyi bankoktól a globálisan függő bankrendszerig - Gál, Zoltán (Közép-Európai Közlemények, 2017)
In this paper we examine the Hungarian banking system in two distinct periods, namely at the turns of the 19/20th and the 20/21st centuries comparing three aspects. We discuss to what extent the development of the banking system followed the international trends and how significant the role of foreign capital was. We also overview the geographical aspects of banking system discussing the changes from the decentralized local banking towards the nation-wide branch banking and recently to the globally dependent monocentric banking system. We argue that the role of banking in economic development was much more direct and important hundred years ago than recently. Concerning the role of foreign capital the paper argues that the Hungarian banking system was more dependent on internal savings in the early 20the century while hundred years later the predominant position of foreign capital and the underlying foreign ownership is the clear sign of dependency on external financing.